PERANCANGAN APLIKASI MOBILE LEARNING BERBASIS ANDROID DI SMK NEGERI 6 PADANG - Rahmat Fadillah; Legiman Slamet (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
Mobile Learning was a learning approach that implicates the mobile devices like smartphone, PDA, tablet PC which the learner was able to access the material, instruction, and application that were relevant to the lesson without being constrained by space and time wherever or whenever they were. Mobile Learning was one of alternative for problem solving in education which comprises the problem of distribution access for education content, content quality, and others. Then, in order to strengthen the source of information for the user and minimized the cost toward the access of that education content. The new inovation for system of study that based on application in systematically and structured as the interactive media for student of  learning process in SMK Negeri 6 Padang. This application could be the appropriate solution for learning in the school and minimize the incorrectness. The design of this system was implementationed by using language of program PHP 7.3.0 with MYSQL of database. In order to design this system involved Used Case Diagram, Activity Diagram, Context Diagram, Flowmap, Normalization, and Entity Relationship Diagram. This system was involved at least 3 users that are Administrator, Teacher, and Student. The registered users have right to access for the system by login with using username and password. This application was designed by using mini server Raspberry Pi 3 model B+ on the web server which based on  Moodle, and platform android as the application for client.Keywords: Mobile Learning, Android, PHP, MYSQL, Moodle.